POTENTIALS AND CHALLENGES RELATED TO ILO RECOMMENDATION NO. 205 ON EMPLOYMENT AND DECENT WORK FOR PEACE AND RESILIENCE - Jašarević, Senad; Božičić, Darko M (Zbornik radova Pravnog fakulteta u Novom Sadu, 2026)
International Labour Organization Recommendation No. 205 on Employment and Decent Work for Peace and Resilience, adopted in 2017, has gone almost unnoticed by our professional public. It is a document that should serve to address the root causes and consequences of instability and to build resilient communities and states in the context of work and working conditions, in the event of crises, wars and similar adverse events.  This paper presents this document in more detail. It also elaborates in more detail the concepts on which the Recommendation is based - "fragility" and "resilience".
Keywords: labour, labour relations, crisis, fragility, resilience